Mifamurtide in metastatic and recurrent osteosarcoma: A patient access study with pharmacokinetic, pharmacodynamic, and safety assessments. Issue 2 (31st August 2013) - Anderson, P.M.; Meyers, P.; Kleinerman, E.; Venkatakrishnan, K.; Hughes, D.P.; Herzog, C.; Huh, W.; Sutphin, R.; Vyas, Y.M.; Shen, V.; Warwick, A.; Yeager, N.; et al.
Abstract Purpose This non‐randomized, patient‐access protocol, assessed both safety and efficacy outcomes following liposomal muramyl‐tripeptide‐phosphatidylethanolamine (L‐MTP‐PE; mifamurtide) in patients with high‐risk, recurrent and/or metastatic osteosarcoma. Methods Patients received mifamurtide 2 mg/m2 intravenously twice‐weekly ×12 weeks, then weekly ×24 weeks with and without chemotherapy. Serum concentration‐time profiles were collected. Adverse events within 24 hours of drug administration were classified as infusion‐related adverse events (IRAE); other AEs and overall survival (OS) were assessed. Results The study began therapy in January 2008; the last patient completed therapy in October 2012. Two hundred five patients were enrolled; median age was 16.0 years and 146/205 (71%) had active disease. Mifamurtide serum concentrations declined rapidly in the first 30 minutes post‐infusion, then in a log‐linear manner 2–6 hours post‐dose; t1/2 was 2 hours. There were no readily apparent relationships between age and BSA‐normalized clearance, half‐life, or pharmacodynamic effects, supporting the dose of 2 mg/m2 mifamurtide across the age range. Patients reported 3, 679 IRAE after 7, 482 mifamurtide infusions. These were very rarely grade 3 or 4 and most commonly included chills + fever or headache + fatigue symptom clusters. One‐ and 2‐year OS was 71.7% and 45.9%. Patients with initial metastatic disease or progression approximated by within 9 months of diagnosis (N = 40) had similar 2‐year OS (39.9%) as the entire cohort (45.9%) Conclusions Mifamurtide had a manageable safety profile; PK/PD of mifamurtide in this patient access study was consistent with prior studies. Two‐year OS was 45.9%. A randomized clinical trial would be required to definitively determine impact on patient outcomes. Pediatr Blood Cancer 2014;61:238–244. © 2013 Wiley Periodicals, Inc.